Correlation between corneal thickness, keratometry, age, and differential pressure difference in healthy eyes - Colakoglu, Ahmet; Colakoglu, Iffet Emel; Cosar, Cemile Banu (NATURE RESEARCH, 2021)
To determine the use of differential pressure difference (DPD), in air-puff differential tonometry, as a potential biomechanical measure of the cornea and elucidate its relationship with the intraocular pressure (IOP), central corneal thickness, corneal curvature, and age. This study comprised 396 eyes from 198 patients and was conducted at Acibadem University, School of Medicine, Department of Ophthalmology, Istanbul, Turkey. The central corneal curvature and refraction of the eyes were measured using an Auto Kerato-Refractometer (KR-1

Topcon Corporation, Tokyo, Japan). IOP and central corneal thickness were measured using a tono-pachymeter (CT-1P

Topcon Corporation, Tokyo, Japan), wherein two separate readings of IOP were obtained using two different modes: 1-30 and 1-60. The difference between these two readings was recorded as the DPD. The factors affecting the DPD were determined by stepwise multiple linear regression analysis. DPD varied over a dynamic range of - 3.0 to+5.0 mmHg and was weakly correlated with the central corneal thickness (r=0.115, p<0.05). DPD showed no significant correlation with IOP 1-30 (p>0.05). A weak but statistically significant (p<0.05) positive correlation of DPD was observed with age (r=0.123), Kavg (r=0.102), and the CCT (r=0.115). There was a significant correlation between DPD and Kavg, CCT, and age. There was no significant correlation between DPD and IOP 1-30. Age-related changes in the corneal ultrastructure may be a plausible explanation for the weak positive association between age and DPD. The proposed method may prove a valid non-invasive tool for the evaluation of corneal biomechanics and introduce DPD in the decision-making of routine clinical practice.